2008
DOI: 10.1097/bpo.0b013e31816c4df8
|View full text |Cite
|
Sign up to set email alerts
|

Shear Stress in Epiphyseal Growth Plate is a Risk Factor for Slipped Capital Femoral Epiphysis

Abstract: III (prognostic study, case-control study).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(18 citation statements)
references
References 27 publications
1
17
0
Order By: Relevance
“…An LCEA of greater than 39°was found in 16.7% (four of 24) of the affected hips, 22.7% (five of 22) of the unaffected hips, and 6.5% (10 of 152) of the controls. Additionally, biomechanical etiology theories of SCFE have demonstrated increase in femoral retroversion, coxa vara, and varus displacement of the load vector will increase physeal shear forces [8,27,38]. The medialization of the femoral head of patients with SCFE (as demonstrated in our study by the increased LCEA) may cause varusization of the force vector, increasing the shear forces across the physis and therefore potentially increasing the risk for SCFE [8,13,25].…”
mentioning
confidence: 73%
See 1 more Smart Citation
“…An LCEA of greater than 39°was found in 16.7% (four of 24) of the affected hips, 22.7% (five of 22) of the unaffected hips, and 6.5% (10 of 152) of the controls. Additionally, biomechanical etiology theories of SCFE have demonstrated increase in femoral retroversion, coxa vara, and varus displacement of the load vector will increase physeal shear forces [8,27,38]. The medialization of the femoral head of patients with SCFE (as demonstrated in our study by the increased LCEA) may cause varusization of the force vector, increasing the shear forces across the physis and therefore potentially increasing the risk for SCFE [8,13,25].…”
mentioning
confidence: 73%
“…While its origin remains an enigma [5,8,27,37,38], treatment methods have continued to evolve [21]. Gelberman et al [10] reported an association of SCFE and femoral retroversion.…”
Section: Introductionmentioning
confidence: 99%
“…Other biochemical or biomechanical factors such as shear stress to the affected and to the opposite hip that contribute to the development of OA may be at work and need further investigation [25,26].…”
Section: Discussionmentioning
confidence: 99%
“…Increased body mass can cause the phenomenon of repetitive microtrauma through the proximal femoral physis to occur with increasingly greater forces. This mechanism, combined with relative femoral retroversion seen in overweight adolescents and the resulting elevated shear stresses, causes physeal chondrocyte apoptosis, biomechanical instability of the physis, and subsequent anterosuperior displacement of the proximal femoral metaphysis relative to the capital epiphysis, which remains contained in the acetabulum [1,19,20,50]. BL-SCFE can occur at the initial presentation, which we labeled concurrent SCFE in the current study, or over time in the contralateral hip, which we labeled sequential SCFE.…”
Section: Discussionmentioning
confidence: 99%